2010
DOI: 10.1063/1.3367721
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic and superspin glass behaviors in the martensitic state of Ni43.5Co6.5Mn39Sn11 magnetic shape memory alloy

Abstract: The magnetic state of the low-temperature martensite in a Ni43.5Co6.5Mn39Sn11 magnetic shape memory alloy (MSMA) is disclosed. At temperatures (T) above a critical temperature Tf, the magnetization versus field [M(H)] curves display a sigmoid shape, show no magnetic hysteresis, and can be well fitted according to the Langevin model, confirming that the martensite shows superparamagnetic behavior at T>Tf. On the other hand, the observation of a memory effect during the stop-and-wait protocol and the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
40
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 21 publications
10
40
2
Order By: Relevance
“…Different magnetic behaviors including paramagnetic [25], antiferromagnetic [26], and reentrant spin glass [27] behaviors have been reported in the literature. Recently, we also observed SPM and SSG behaviors in the martensitic state of a Ni 43.5 Co 6.5 Mn 39 Sn 11 alloy [12]; the SPM martensite of that alloy is directly transformed from the ferromagnetic austenite, and a transition sequence of ferromagnetic austenite-SPM martensite -SSG martensite is followed. Nevertheless, it remained an open question whether the SPM and SSG behaviors of martensite are unique only in that particular alloy.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Different magnetic behaviors including paramagnetic [25], antiferromagnetic [26], and reentrant spin glass [27] behaviors have been reported in the literature. Recently, we also observed SPM and SSG behaviors in the martensitic state of a Ni 43.5 Co 6.5 Mn 39 Sn 11 alloy [12]; the SPM martensite of that alloy is directly transformed from the ferromagnetic austenite, and a transition sequence of ferromagnetic austenite-SPM martensite -SSG martensite is followed. Nevertheless, it remained an open question whether the SPM and SSG behaviors of martensite are unique only in that particular alloy.…”
Section: Methodsmentioning
confidence: 88%
“…The lack of information on these aspects has greatly hindered further attempts to optimize the functional properties of these alloys. Quite recently, we investigated the magnetic properties of martensite in a Ni 43.5 Co 6.5 Mn 39 Sn 11 MSMA [12]. However, as the phase transformation and magnetic properties of the Ni-Co-Mn-Sn alloys are highly sensitive to their chemical composition, alloys with different composition should be studied in order to gain a comprehensive understanding of the structural and magnetic transitions in this alloy system.…”
Section: Introductionmentioning
confidence: 98%
“…Although the breakthrough in spintronics was achieved due to multilayer structures, granular materials based on the Heusler alloys have also been thoroughly studied as potential spin-injector materials. The experimental investigation of their electronic transport and magnetostructural transitions [1][2][3][4][5] as well as theoretical models and calculations predicting the effects of the spin-polarized medium [6][7][8][9] is presented in numerous works. They have shown that the magnetic and transport properties of the granular materials are defined by a combination of different factors such as preparation and treatment conditions, and the choice of the matrix compounds, as well as combinations of the interparticle distance, size and magnetic moments of particles.…”
Section: Introductionmentioning
confidence: 99%
“…the issue of whether the background martensitic matrix is in fact paramagnetic or AF, the spatial range of the F and AF spin correlations, and the true nature of the freezing transition. Regarding the latter issue, it has been suggested, by a number of authors [19,20], that the freezing of the spin clusters is actually collective, obviously requiring strong inter-cluster interactions, leading to a so-called "super-spinglass" state. Additionally, it is now clear, from a number of works [e.g.…”
Section: Introductionmentioning
confidence: 99%